Cybersecurity and Moral Responsibility: A Philosophical-Islamic Approach to Digital Trust - Alif Auladi, Ghifari; Muwahid, Fathan (TechComp Innovations: Journal of Computer Science and Technology, 2025)
The dominance of Western-centric norms in cybersecurity ethics presents a significant gap in addressing the moral and cultural realities of diverse societies, particularly those in the Muslim world. This paper proposes a decolonial and culturally inclusive framework by integrating Islamic ethical philosophy into the discourse on cybersecurity. Drawing on key Islamic concepts such as amanah (trust), ‘adl (justice), and niyyah (intention), the study explores how these values can inform ethical decision-making in digital environments. Through a philosophical-theological approach, it critiques the assumption of value neutrality in technology and highlights the moral agency and accountability embedded in Islamic metaphysics. The findings underscore the necessity of ethical pluralism and call for a global digital ethics that is both morally substantive and culturally responsive. Ultimately, the study contributes to the development of a more holistic and spiritually informed cybersecurity paradigm that resonates with the ethical traditions of Muslim-majority contexts.